CARBON STOCKS IN MANGROVE FORESTS AT MANGROVE FORESTS LEARNING AND DEVELOPMENT CENTER 2, NAKHON SI THAMMARAT - Srimoh, Rinlanee; Markphan, Wattananarong (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The amount of carbon stored in mangrove forest plants studied at the 2nd Mangrove Forest Resource Development and Learning Center in Nakhon Si Thammarat. A total of 6 sampling plots of 20 x 50 m, Only the first sample obtained with this technique, then subsequent samples evenly spaced apart. Plant identification, counting, the process is recording the DBH (diameter at breast height), the height as well as for plant species list and plant family list of trees (DBH >4.5 cm and height >1.30 m). then calculated the biomass by using the allometric equation. According to the study's findings, there are 6 species and 5 families of trees in the mangrove plant community. Avicennia marina (Forsk) is the dominant tree with the highest value of importance index, followed by Rhizophora apiculata Blume, Lumnitzera racemosa Willd, with importance index values of 77.67, 76.36 and 62.04 percent, respectively. The large trees are typically 8.22±1.93 m in height and have an average diameter of 14.68±4.28 cm, A total of 18 rai of the mangrove forests around the Center for Learning and Development of Mangrove Forest Resources 2nd have an accumulation of biomass that is equal to 10,104.12 kg per rai, with an overall carbon accumulation of 85.48 tons, or 4.75 tons per rai.